Effects of bushen qianggu method for primary osteoporosis: A protocol for systematic review and meta-analysis. Issue 24 (12th June 2020) - Chen, Guocai; Guan, Yingxin; Ye, Xiangling; Chen, Guoqian; Du, Jianping; Liu, Wengang; Zhao, Chuanxi; Yao, Nan; Xu, Xuemeng
Abstract: Background: Primary osteoporosis (POP) is one of the most common orthopedic diseases with a high risk of fracture. Effective treatment of POP is of great significance to reduce the rate of disability and improve the quality of life. Bushen qianggu (BSQG) is a classical method of TCM in treating POP. However, there is no systematic review related to BSQG for POP. The purpose of this study is to provide a comprehensive and reliable evaluation of the clinical evidence of BSQG in the treatment of POP. Methods and analysis: Relevant randomized controlled trial literature evaluating the effect of BSQG on patients with POP will be obtained by searching the PubMed, Embase, MEDLINE, Cochrane Library Central Register of Controlled Trials, China national knowledge infrastructure database, Wan fang database, Chongqing VIP information, and SinoMed from their inception to May 2020. Two researchers will select and evaluate qualified studies independently. The bone mineral density value and the incidence of fractures will be accepted as the primary outcomes. The meta-analyses will be performed by using the RevMan 5.3. Results: This study will provide a comprehensive evaluation of the efficacy and safety of BSQG method for patients with POP. Conclusion: The conclusion of our systematic review will provide evidence to judge whether BSQG is an effective intervention for patients with POP. Trial registration number: 10.17605/OSF.IO/ZMX3W.